2004
DOI: 10.1097/01.ju.0000125487.96469.2e
|View full text |Cite
|
Sign up to set email alerts
|

Young Age Is an Independent Prognostic Factor for Survival of Sporadic Renal Cell Carcinoma

Abstract: Young adults with RCC were more likely to have unfavorable histological features and a higher incidence of lymph node metastases than an older cohort of adults. Despite these differences on multivariate analysis young patients had improved disease-specific and recurrence-free survival following treatment. Whether age specific differences in host-tumor interaction exist in patients with RCC deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
7
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 14 publications
9
53
7
3
Order By: Relevance
“…Unfortunately, we cannot directly compare the results of our study with those in other cohorts becaused none used similar methodology. Despite the methodological distinctness of our study, we did corroborate the findings of Sánchez-Ortiz and colleagues 3 and of Taccoen and colleagues, 4 namely, that young age exerts a protective effect against RCC-SM. The novelty of our findings resides in the breakpoints that differ from previous studies that used the age of 40 years as a cut-off.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Unfortunately, we cannot directly compare the results of our study with those in other cohorts becaused none used similar methodology. Despite the methodological distinctness of our study, we did corroborate the findings of Sánchez-Ortiz and colleagues 3 and of Taccoen and colleagues, 4 namely, that young age exerts a protective effect against RCC-SM. The novelty of our findings resides in the breakpoints that differ from previous studies that used the age of 40 years as a cut-off.…”
Section: Discussionsupporting
confidence: 81%
“…3,10,12,13 Recently, 2 studies indicated that better survival could be expected in young patients and that age was an independent predictor of RCC-SM. 3,5 These 2 studies involved 106 and 4774 patients, respectively. Both used an age cutoff of 40 years, which was consistent with cut-offs tested in previous studies of RCC and with cut-offs used in studies of other cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite no agreement on the exact age limit in order to consider patients with RCC as young adults. Several studies accepts 35-45 years as the upper limit [2,6,10] and 14-26 as the lower limit [1][2][3]7,11]. Additionally, some of the studies even included benign lesions of the kidney in their series [5,12] which we think affect interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] This association has previously been validated in renal cell carcinoma. 7,8 It is possible that such tumours in younger patients are associated with more aggressive genomic alterations. 9,10 However, these hypotheses have never been tested in the context of UCUB.…”
Section: Introductionmentioning
confidence: 99%